Spoligologos: A Bioinformatic Approach to Displaying and Analyzing Mycobacterium tuberculosis Data - Driscoll, Jeffrey R. (Centers for Disease Control and Prevention, 2002)
Spacer oligonucleotide (spoligotyping) analysis is a rapid polymerase chain reaction–based method of DNA fingerprinting the Mycobacterium tuberculosis complex. We examined spoligotype data using a bioinformatic tool (sequence logo analysis) to elucidate undisclosed phylogenetic relationships and gain insights into the global dissemination of strains of tuberculosis. Logo analysis of spoligotyping data provides a simple way to describe a fingerprint signature and may be useful in categorizing unique spoligotypes patterns as they are discovered. Large databases of DNA fingerprint information, such as those from the U.S. National Tuberculosis Genotyping and Surveillance Network and the European Concerted Action on Tuberculosis, contain information on thousands of strains from diverse regions. The description of related spoligotypes has depended on exhaustive listings of the individual spoligotyping patterns. Logo analysis may become another useful graphic method of visualizing and presenting spoligotyping clusters from these databases.